Blood transfusions in gunshot‐wound‐related emergency department visits and hospitalizations in the United States. Issue 8 (2nd July 2021) - Goel, Ruchika; Zhu, Xianming; Makhani, Sarah; Petersen, Molly R.; Josephson, Cassandra D.; Katz, Louis M.; Shaz, Beth H.; Austin, Richard; Crowe, Elizabeth P.; Ness, Paul M.; Gehrie, Eric A.; Frank, Steven M.; et al.
Abstract: Background: The United States (US) leads all high‐income countries in gunshot wound (GSW) deaths. However, previous US studies have not evaluated the national blood transfusion utilization patterns in hospitalized GSW patients. Methods: Data from 2016 to 2017 were analyzed from the Nationwide Emergency Department Sample (NEDS) and Nationwide Inpatient Sample (NIS), the largest all‐payer emergency department (ED) and inpatient databases, respectively. Using stratified probability sampling, weights were applied to generate nationally representative estimates. Multivariable Poisson‐regression models were used to estimate prevalence ratios (PR) of blood transfusion. Results: There were 168, 315 ED visits and 58, 815 hospitalizations (age = 18–90 years) following a GSW. The majority of hospitalizations were men (88.5%), age 18–24 years (31.8%), and assault‐related GSW (51.3%). Blacks had the largest proportion (48.7%) overall of all GSW hospitalizations; Whites accounted for the highest proportion of intentional self‐harm injuries (72.4%). Blood transfusions occurred in 12.7% of hospitalizations (12.0% red blood cell [RBC], 4.9% plasma, and 2.5% platelet transfusions). Only 1.9% of cases were associated with transfusion of all three blood components. Hospitalizations with major/extreme severity of illness had significantly higher prevalence of transfusion versus those with mild/moderate severity [crude PR = 4.79 (95%CI:4.15–5.33, p  < .001)]. Overall, 8.2% of hospitalizations with GSW died, of whom 26.8% required blood transfusions, which was significantly higher than survivors [crude PR = 2.34 (95%CI:2.10–2.61, p  < .001)]. The vast majority (95%) of the transfusions among those who died were within 48 h since admission. Conclusions: Gun‐related violence is a public health emergency in the US, and GSWs are a source of significant mortality, blood utilization, and health care costs.